Affluence and High Household Liquidity: Problems and Opportunities - Martin, Preston (Journal of Financial and Quantitative Analysis, 1966)
Preston Martin, Affluence and High Household Liquidity: Problems and Opportunities, The Journal of Financial and Quantitative Analysis, Vol. 1, No. 1, Proceedings of the First Annual Meeting of the Western Finance Association (Mar., 1966), pp. 30-53